Étude de l'impact des interactions culturelles sur les occupants de l'Habitation 1 de Double Mer Point : développement d'une nouvelle méthodologie pour l'étude des sites de contacts - Pouliot, Laurence (Université Laval, 2020)
Through the Tradition and Transition among Labrador Inuit partnership between the Nunatsiavut Government and the Memorial University of Newfoundland, the extensive archaeological excavation undertaken at Double Mer Point (GbBo-02) allowed us to study the impact of cultural interactions in Labrador on the daily life of the inhabitants of House 1 during the contact period, between the 17th and 19th centuries, a subject still under-exploited by archeology. Theoretical ideas from cultural contact studies and postcolonial archeology have thus been applied to Labrador through this research. Our theoretical reflection about the study of material culture from the contact period led to the development of a methodology combining the cultural aspects of objects and their manufacture. House 1, a semi-subterranean sod house dated from the late 18th and early 19th century, was interpreted using data (material, zooarchaeological, architectural and environmental) collected directly in the field. The dating of the site, the occupation phases and activities areas were determined via various analyzes. House 1 revealed a more complex occupation than most of the semi-subterranean houses of this period. It suggests of several phases of occupation of which the first would be a prehistoric Dorset occupation while the last one demonstrates the integration of a European in an Inuit community. The application of our methodology allows us to identify direct cultural transfers, to observe the intensification of intrinsic cultural traits, to study the influence of new material in the daily life of a community and to assess the impact of these changes in Labrador. This thesis contributes to the reconstruction of the cultural history of Labrador and hopes to encourage research about cultural interactions and material culture of the contact period. Grâce au partenariat Tradition and Transition among Labrador Inuit unissant le Gouvernement Nunatsiavut et l'Université Mémorial de Terre-Neuve, la fouille exhaustive du site Double Mer Point ...